Mediation in custody disputes: challenges and prospects in Malaysia - Abdul Hak, Nora (Institut Sosial Malaysia & Faculty of Human Ecology, UPM, 2012)
In dealing with custody disputes especially, mediation is generally considered as a process more humane than the confrontational approach taken in the adversarial system, (Pearson and Thoennes 1989). Mediation is claimed to not only avoid adversary settlement procedures, but also to be a „family-friendly‟ intervention program employed in helping post-separating families deal with divorce and conflict (Emery et al. 2005).The focus of mediation is encouraging the parties to solve their conflict amicably. Moreover, according to Vincent (1996, p.264), in mediation involving custody disputes, the decision about the children‟s future is shifted to their parent: the people who know them best. Other commentators, including Menkel-Meadow (1991) and Sander (1984), also maintain that the informal and flexible nature of the mediation process enables the parties to address issues that might not be raised in a more formal dispute settlement approach. In fact, rather than restricting the decision making process to legal matters, mediation accommodates to the prospective needs and interest of the parties, leading to a whole and more satisfactory resolution in most cases. Thus, the paper will focus on the use of mediation in custody disputes looking at the nature of mediation, its advantages and disadvantages; and its challenges and future in Malaysia.